2020
DOI: 10.21203/rs.3.rs-17640/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Improving phage titre through examining point of infection

Abstract: Bacteriophages are viruses that cause the lysis of bacteria. They have recently been used to combat antimicrobial resistant infections as an alternative therapy to antibiotics. Their production and propagation, however, remains understudied and will be key to obtaining titres required for future clinical studies and research. Previous work suggests that temperature of infection significantly influences the production process and output yield of phage, with a reduction in temperature from 37ºC to 28ºC resulting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…One historical study by Pollard et al demonstrated using different temperatures to obtain differential titers [49]. Another example is the lowering of the infection temperature for E. coli-T4 [50,51]. Grieco et al reported that in a Design of Experiment study where the effect of DO, pH, and temperature was tested for optimal yield, the optimal theoretical yield (2.86 × 10 11 PFU/mL) was achieved at 28.1 • C and a pH of 6.9 which was validated with empirical studies (3.49 × 10 11 PFU/mL).…”
Section: Phage Engineering Opportunities and Challenges In Uspmentioning
confidence: 99%
“…One historical study by Pollard et al demonstrated using different temperatures to obtain differential titers [49]. Another example is the lowering of the infection temperature for E. coli-T4 [50,51]. Grieco et al reported that in a Design of Experiment study where the effect of DO, pH, and temperature was tested for optimal yield, the optimal theoretical yield (2.86 × 10 11 PFU/mL) was achieved at 28.1 • C and a pH of 6.9 which was validated with empirical studies (3.49 × 10 11 PFU/mL).…”
Section: Phage Engineering Opportunities and Challenges In Uspmentioning
confidence: 99%